Propriedades dielétricas intrínsecas de óxidos cerâmicos com estruturas perovskita e scheelita - Lima, Pedro Henrique Moreira (2024)
In this thesis, we conducted an investigation of how extrinsic and, mainly, intrinsic factors can influence vibrational, structural, magnetic, and dielectric properties for different classes of perovskites and oxides. In the first case, we evaluated rare-earth orthoferrites doped with Ni, GdFe1−xNixO3 (x = 0.0, 0.1, and 0.2), where we observed how the insertion of Ni influenced the vibrational properties and intrinsic dielectric responses of these materials. Initially, we studied the structure and composition through powder X-ray diffraction, which revealed an increase in structural distortions caused by the Ni atoms. Magnetometry demonstrates the relevant role of Ni in magnetic transition, magnetization, and coercive field. Infrared reflectance spectroscopy was applied to evaluate the intrinsic dielectric response, which is very useful in telecommunication electronic devices. Analysis of the spectra using the four-parameter model reveals a strong influence of vibrational modes below 250 cm−1, related to Gd ions and the (Fe/Ni)O6 structure, on the static permittivity of the materials. Samples of orthovanadates with different rare-earth elements were also investigated, ReVO4 (Re = Ho, Tm, and Yb). The materials, analyzed using powder X-ray diffraction and infrared reflectance spectroscopy, revealed that despite being structurally very similar, their intrinsic dielectric responses are quite different, with a notable influence from the initial vibrational modes associated with the translation of rare-earth atoms. Finally, but not least, we investigated the vibrational and intrinsic dielectric properties of the double perovskite La2CoMnO6 (LCMO) at low temperatures in order to gain a better understanding of spin-phonon coupling and the implications of this interaction on the intrinsic dielectric response. Through an in-depth study conducted on infrared spectra in the region of the critical magnetization temperature, we observe significant changes in modes and divergent behaviors for dielectric responses such as quality factor and intrinsic dielectric constant are noticeable, where an inverse relationship between permittivity and factor with temperature variation was observed.